2023
DOI: 10.1186/s12967-023-04239-8
|View full text |Cite
|
Sign up to set email alerts
|

DHA supplementation and pregnancy complications

Abstract: Docosahexaenoic acid (DHA) supplementation is recommended for women during pregnancy because of its neurological, visual, and cognitive effects. Previous studies have suggested that DHA supplementation during pregnancy may prevent and treat certain pregnancy complications. However, there are contradictions in the current related studies, and the specific mechanism by which DHA acts remains unclear. This review summarizes the research on the relationship between DHA intake during pregnancy and preeclampsia, ges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 155 publications
0
2
0
Order By: Relevance
“…The lack of DHA due to GDM may further promote dysbiosis in the fetal microbiome, as DHA helps maintain the microbiome’s Firmicutes/Bacteroidetes ratio and promotes the abundance of anti-inflammatory species ( Muley and Plessis, 2018 ). As a result, providing high doses of DHA may increase the amount of DHA in the cord blood of GDM patients ( Jiang et al, 2023a ). Furthermore, GDM, the associated dysbiosis of the maternal gut microbiota, and the resulting impacts on metabolite delivery to the fetus should be studied.…”
Section: Effects Of Gdm On Gut Microbiota-derived Metabolites In Feta...mentioning
confidence: 99%
“…The lack of DHA due to GDM may further promote dysbiosis in the fetal microbiome, as DHA helps maintain the microbiome’s Firmicutes/Bacteroidetes ratio and promotes the abundance of anti-inflammatory species ( Muley and Plessis, 2018 ). As a result, providing high doses of DHA may increase the amount of DHA in the cord blood of GDM patients ( Jiang et al, 2023a ). Furthermore, GDM, the associated dysbiosis of the maternal gut microbiota, and the resulting impacts on metabolite delivery to the fetus should be studied.…”
Section: Effects Of Gdm On Gut Microbiota-derived Metabolites In Feta...mentioning
confidence: 99%
“…Low maternal DHA status in human pregnancy is associated with learning, cognitive, motor and visual disorders in children (for a review, see [10]). Evidence that DHA supplementation in pregnancy improves cognitive function, learning or vision in the children of supplemented women has been inconsistent, with some studies showing improvement but not all [13][14][15]. A study of women with Gestational Diabetes Mellitus (GDM) found that the mothers had higher DHA dietary intake and RBC levels, while their infants were deficient in DHA and suffered from increased neurological sequelae [16].…”
Section: Introductionmentioning
confidence: 99%